The effect of different irrigation frequencies in combination with boron and calcium bunch applications on berry split of SoutherngrapeOne - Koekemoer, Abraham Leander (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2010.